Digital preservation for businesses: a bibliometric study of scientific production in Brapci (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The article "Digital Preservation for Companies: A Bibliometric Study of Scientific Production in BRAPCI" presents a detailed analysis of academic production on digital preservation in the business context, based on the Reference Database of Periodicals Articles in Information Science (BRAPCI). Using a quali-quantitative approach, the research identified and quantified publications related to the topic between 1997 and 2022. 729 results were found, distributed between articles and event proceedings, with a total of 732 authors and co-authors. The study highlighted the evolution of the number of publications over time, with a significant increase in the last decade. In addition, the article discusses the importance of the LAI (Access to Information Law) and LGPD (General Data Protection Law) in digital preservation, emphasizing the need for robust strategies to ensure the integrity and accessibility of digital documents. The study brings the discussion about the subject and the techniques most addressed by the authors who stand out in the area.
Keywords: digital preservation; chain of custody; bibliometrics